STRATEGI KOMUNIKASI PEMASARAN DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN BENGKALIS DALAM MEMPROMOSIKAN PRODUK INDUSTRI KECIL DAN MENENGAH - Pajrianti, Desi; Lubis, Evawani Elysa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Economic growth in the era of globalization is characterized by the development of the business world , industry sector One of them is the Small and Medium Enterprises ( SMI). The importance of SMI sector in Indonesia is to equalize the population economy, as well as to support the development of other sectors . In order to achieve the goals and objectives of SMI products in Bengkalis be known by the public , the Department of Industry and Trade Bengkalis use marketing communication strategy in order to run an effective marketing. Therefore, researchers interested in conducting research with the aim to determine the communication strategy of the Department of Industry and Trade Bengkalis in promoting SMI products . This research uses qualitative methods, namely the collection of data obtained based on the fact data in the field through observations, interviews, documentation and interactive data analysis techniques. researchers conducted interviews with three groups of informants . The first informant group consisted of 4 people from the Department of Industry and Trade Bengkalis regency . The second informant group consisted of 3 people from the perpetrators of SMI and the third group consisted of 4 from consumers . The first and second groups of informants using purposive sampling techniques , while the third group are selected using accidental sampling technique . Results of this research indicate that the marketing communication strategy Department of Industry and Trade Bengkalis in promoting SMI products using segmentation strategy , targeting, and positioning . After determining the strategy of segmentation, targeting, and positioning. the Department of Industry and Trade Bengkalis also perform elements of marketing communications which consist of advertising, sales promotion , personal selling , direct marketing , publicity and public relations. Other marketing communication strategy is to use Packaging to launch a strategy to promote SME products . Key Words: Marketing communication strategy, Promotion, ProductSmall and Medium Industries (SMI)